Systematic Literature Review on the Effectiveness of the Cooperative Learning Models in Improving Collaboration and Social Skills of Elementary School Students - Pebriana, Putri Hana; Misnati , Kesi; Jeniari , Felisa; Azzikra , Rahma; Nurhayati , Nurhayati; Andina , Farah Zhefira; Fitri , Desrina Wanti; Zhefira , Nabila (The Future of Education Journal, 2025)
This research is designed to assess the effectiveness of cooperative learning models in enhancing the collaboration and social skills of elementary school (SD) students. The study employs the Classroom Action Research (PTK) approach, which follows a cyclical design that includes stages of planning, implementation, observation, and reflection. The participants in the study were 25 fourth-grade students. The results indicate that cooperative learning strategies, particularly the Jigsaw and Think-Pair-Share methods, play a significant role in improving students’ social interactions, teamwork, and communication abilities. These strategies encourage active participation and foster a more inclusive classroom environment where students learn from each other, share ideas, and work together toward common goals. The findings underline the value of cooperative learning models not only in academic achievement but also in building essential social skills. By engaging in collaborative tasks, students develop problem-solving skills and learn how to express their thoughts clearly and respectfully, which are crucial skills for their overall development. Moreover, these methods promote a positive classroom culture where students support each other’s learning processes, making the learning experience more dynamic and enjoyable. As such, these cooperative learning techniques can be viewed as an effective and beneficial approach that should be integrated into elementary school curricula to foster not only academic success but also social competence among students.